Massive obstetrics haemorrhage: our experience - K, Balasudha; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to analyze the clinical profile, treatment modalities and outcome of patients with massive obstetric haemorrhage. Methods: All patients who delivered in the department of Obstetrics and Gynaecology PSG Institute of Medical Sciences, Coimbatore between Jan 2012 to Dec 2012 were analyzed. There were 2339 deliveries in this period. Of these there were 17 patients with serious obstetric haemorrhage who required blood transfusion giving an incidence of 0.73%. All the patients who fulfilled the criteria of massive obstetric haemorrhage were analyzed. Results: Past Of the 2339 deliveries from Jan 2012 to Dec 2012 there were 17 patients with serious haemorrhage. Out of these four patients who had massive obstetric haemorrhage are presented in this study. Conclusions: Obstetric haemorrhage continues to be the leading cause of maternal mortality in India. Initial resuscitation with simultaneous identification of the cause and definitive treatment is important.